(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Some effects of monosodium glutamate that is commonly used as food additive and flavor enhancer were evaluated on histological, and biochemical parameters on neocerebellar cortical structures in adult Wistar rats following monosodium glutamate induced toxicity. Forty eight adult male Wistar rats weighing between 70-130g (8-10 weeks old) were randomly separated into four groups, each containing twelve rats. The rats in group A were regarded as the controls and they received only distilled water during the treatment period. The rats in group B, C and D were MSG-treated rats. The Wistar rats in group B, C and D received respectively 2g/kg, 4/kg and 6g/kg body weight of MSG orally once duty for 28 consecutive days. The rats were euthanized on 29th day of the treatment. The cerebellum were carefully dissected out before removing halves of the neocerebellar cortical tissues for the preparation of the homogenate samples for assessment of oxidant and antioxidant parameters, Lipid peroxidation( LPO); malondialdehyde (MDA), super oxide dismutase (SOD), catalase (CAT) glutathione (GSH) and nitric oxide (NO). The remaining neocerebellar and neocerebral cortical samples were fixed immediately in 10% buffered formal saline for routine histological procedures for evaluation by light microscopy. The results from tissue analysis on oxidant and antioxidant parameters indicated a dose-dependent, significant increased (P<0.05) in lipid peroxidation (LPO) and nitric oxide (NO) in the neocerebellar cortical tissues in MSG-treated rats compared with controls. Conversely, the cortical SOD, CAT and GSH decreased significantly (P<0.05) in MSG-treated rats compared with controls. This histological findings from the MSG – treated rats demonstrated some atrophic and neurodegenerative changes in the cortical neurons. Some neocerebellar Purkinje cells appeared shrunken, pyknotic and degenerative coupled with vacuolization of the neuropile or stroma of the cortex. Conversely, the neocortical sections from the control rats appeared normal as the cortical neurons showed regular outlines. This study concluded that prolonged exposure to MSG may result in neocerebellar cortical damage which might be due to oxidative stress induced by excitotoxicity of MSG and consequently the cerebellar functions might be compromised.